Les dynamiques territoriales de l’industrie du jeu vidéo en France - Hovig Ter Minassian (Territoire en Mouvement)
The videogame industry in France is today a dynamic but fragile sector. However, its functioning and its various actors who are still insufficiently documented. In this text, we focus on its spatial dimension. We mobilize the concepts of “territorialization” and «proximity» to understand the logics of its diffusion on a national scale. Our qualitative survey conducted between 2016 and 2018 allows us to come to three main results. The sector is characterized by a great heterogeneity, both in terms of actors and territorial development strategies. This is all the more true since each territory studied takes advantage of generic tools and specific local resources in a logic of differentiation. Finally, it is important to stress the importance of local anchoring as a development strategy in its own right, which requires the production and mobilization of localized resources in order to create proximity between the various actors of the territory.